2D/2D Bi2MoO6/g-C3N4 S-scheme heterojunction photocatalyst with enhanced visible-light activity by Au loading. (1st November 2020) - Li, Qiaoqiao; Zhao, Wenli; Zhai, Zicheng; Ren, Kaixu; Wang, Tingyu; Guan, Hao; Shi, Haifeng
Abstract: A novel 2D/2D Bi2 MoO6 /g-C3 N4 step-scheme (S-scheme) composite by loading Au as cocatalyst was successfully fabricated using a photoreduction and hydrothermal route. The obtained Bi2 MoO6 /g-C3 N4 /Au photocatalysts were characterized by X-ray diffraction (XRD), transmission electron microscope (TEM), X-ray photo-electron spectroscopy (XPS), UV–vis diffuse reflectance spectra (UV–vis), Fourier transform infrared spectroscopy (FTIR), photoluminescence (PL), photocurrent response( I - t ), and electrochemical impedance spectroscopy (EIS). The HRTEM images revealed that an intimate interface in composites were formed. The optimum photocatalytic activity of Rhodamine B degradation over Bi2 MoO6 /g-C3 N4 /Au was about 9.7 times and 13.1 times as high as those of Bi2 MoO6 and g-C3 N4, respectively. The notably improved photocatalytic activity of Bi2 MoO6 /g-C3 N4 /Au could be mainly ascribed to the abundant active sites and the enhanced separation efficiency of photogenerated carriers in Bi2 MoO6 /g-C3 N4 S-scheme system. Notably, Au nanoparticles could act as a co-catalyst to further promote electron transfer and separation from the conduction band of g-C3 N4 . Additionally, a possible step-scheme photocatalytic reaction mechanism of RhB degradation over Bi2 MoO6 /g-C3 N4 /Au was tentatively proposed. PL and transient photocurrent analysis implied that Bi2 MoO6 /g-C3 N4 /Au photocatalysts possessed the lower recombination rate of photogenerated carriers compared with pure Bi2 MoO6 and g-C3 N4, respectively. The present work is expected to provide useful information in designing 2D/2D S-scheme heterojunction photocatalysts.